2012
DOI: 10.1002/macp.201200294
|View full text |Cite
|
Sign up to set email alerts
|

Poly(phenylnorbornene) from Ring‐Opening Metathesis and Its Hydrogenated Derivatives

Abstract: Novel polymers are synthesized from 5‐phenyl‐2‐norbornene (PhNb) and its saturated side group analog, 5‐cyclohexyl‐2‐norbornene, using ring‐opening metathesis polymerization (ROMP). Polymers of both endo‐rich and all‐exo PhNb show glass transition temperatures (Tg) = 88 ± 1 °C, indicating a negligible effect of monomer stereoisomerism on segmental packing or the energy barriers to motion at the glass transition, despite the substantial size of the side group. Post‐polymerization hydrogenation of the PhNb polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Hydrogenation of polynorbornenes can be achieved by various routes—including both catalytic saturation over palladium or a Ni/Al complex, or via the generation of reactive diimide molecules in situ as the hydrogen source . Gel permeation chromatography conducted on ROMP polymers of 5‐substituted norbornenes (which are soluble at room temperature both before and after hydrogenation) has demonstrated that all of these hydrogenation methods proceed without significant chain scission or coupling . However, while a variety of ROMP hPNs and hPN‐containing copolymers have been reported, no other effects of the choice of hydrogenation route on the semicrystalline product have been previously considered.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of polynorbornenes can be achieved by various routes—including both catalytic saturation over palladium or a Ni/Al complex, or via the generation of reactive diimide molecules in situ as the hydrogen source . Gel permeation chromatography conducted on ROMP polymers of 5‐substituted norbornenes (which are soluble at room temperature both before and after hydrogenation) has demonstrated that all of these hydrogenation methods proceed without significant chain scission or coupling . However, while a variety of ROMP hPNs and hPN‐containing copolymers have been reported, no other effects of the choice of hydrogenation route on the semicrystalline product have been previously considered.…”
Section: Introductionmentioning
confidence: 99%
“…Under the conditions employed the final product consisted of both endo and exo isomers in an 80/20 ratio, respectively, based on the integration of the olefinic region in the 1 H NMR spectrum. Assignments of olefinic resonances to the endo or the exo isomer is based on analogous resonances found for 5‐phenyl‐2‐norbornene in which the endo isomer exhibited a larger separation between the two olefinic proton resonances than that observed for the exo isomer …”
Section: Resultsmentioning
confidence: 94%
“…For example, as summarized in Figure 1, poly(norbornene) derivatives containing endo ‐ester and endo ‐cyano substituents exhibit glass transition temperatures that are approximately 40°C higher than their exo ‐analogues, 22 although the origin of the differences could not be exclusively attributed to electronic or steric effects. In contrast, polymers synthesized from mono‐substituted endo ‐ or exo ‐phenyl norbornene exhibit no significant differences in their respective glass transition temperature values 17,23 . The paucity of studies may be due in part to catalyst limitations as diminished polymerization rates have been observed with monomers that feature endo ‐substituents 22,24–33 .…”
Section: Introductionmentioning
confidence: 99%
“…Each of these features effectively constrain bond rotation along the polymer backbone in a manner that can significantly affect the thermal properties displayed by the corresponding polymers. For example, cis ‐poly(norbornene) exhibits a T g at a temperature that is approximately 30°C higher than its trans analogue 14–18 . Likewise, the T g s of various endo ‐poly(norbornene‐dicarboximide) derivatives are approximately 30–40°C higher than their exo analogues.…”
Section: Introductionmentioning
confidence: 99%